Iceberg disturbance to benthic communities in McMurdo Sound, Antarctica. (25th March 2021) - Kim, Stacy; Collins, Clint A.
Abstract: On the continental shelf of the Antarctic the major disturbance to benthic ecosystems is from iceberg scouring; however, this is based on observations from the Peninsula region. We combine observation and experimentation in the McMurdo Sound region of the Ross Sea to determine if community recovery patterns there are similar to those in better-studied Antarctic regions, and if local immigration is an important factor in recovery dynamics. We found that regardless of habitat differences in depth, substrate, and oceanographic setting, iceberg disturbance strongly impacted benthic communities in McMurdo Sound. Notably, in shallow water (<30 m) where anchor ice is an annual disturbance, both the benthic communities and recovery processes were more variable than at deeper locations. A manipulative experiment performed in a shallow area indicated that recruitment might be more important than immigration to infaunal community recovery. We conclude that whilst disturbance frequency influences dominant epifauna, recovery from iceberg disturbance is a slow ecological progression that is dependent on the extremely inconsistent recruitment processes of the high Antarctic benthic ecosystem.